Analisis Peminatan Siswa SMA terhadap Prodi Akuntansi Publik Secara Digital - Gladys Farah Diba; Hurian Kamela (AKUNTANSI 45, 2025)
High school students' interest in digital-based Public Financial Accounting is influenced by various interrelated factors. This article aims to analyze the level of interest of high school students in Public Financial Accounting in the context of digital development. This study used quantitative methods with a survey approach to identify factors influencing this interest. The results indicate that students' perceptions of accounting knowledge play a significant role in shaping their interest in this field. Furthermore, students' views on job prospects in public financial accounting, particularly digital-based ones, also influence their decision to choose a study program. The role of teachers and parents has also proven significant in providing guidance, motivation, and initial understanding of the importance of accounting in public financial management. However, some students still lack a comprehensive understanding of the scope and role of Public Financial Accounting. Therefore, schools are expected to increase their outreach efforts and innovative learning to attract students' interest in studying Public Financial Accounting digitally.